Old Strategies and New Perspectives in Modulating the Endocannabinoid System - Antonella, Brizzi; Federica, Pessina (Current Bioactive Compounds, 2019)
Endocannabinoid System (ES) has gained over the years a leading position in scientific research thanks to its involvement in numerous patho/physiological conditions. Accordingly, its main components, such as receptors, enzymes and mediators, have become important drug targets for the management of diseases where it is dysregulated. Within the manuscript, several classes of cannabinergic ligands are examined, emphasizing molecules coming from the natural world, unique source of active compounds. Firstly, the endogenous lipid ES modulators are described, starting from the major endocannabinoids to the plethora of endocannabinoid congeners. Afterwards, Cannabis-derived cannabinoids, namely well-known phytocannabinoids and new constituents from different varieties of Cannabis, are reviewed also mentioning the huge effort of pharmaceutical research in obtaining synthetic analogues. Finally, an overview of peptides and miscellaneous natural products points out new opportunities to modulate ES, offering an enormous chemical heterogeneity. Accordingly, hemopressin and related peptides, plant-derived alkylamides, terpenoid derivatives, neolignans and examples from the marine world can provide interesting hints and original ideas to develop new cannabinergic compounds.
Keywords: phytocannabinoids